2019
DOI: 10.3390/su11082441
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Alkalization and Temperature on Ammonia Recovery from Cow Manure and the Chemical Properties of the Effluents

Abstract: Manure is a substantial source of ammonia volatilization into the atmosphere before and after soil application. The purpose of the study was to investigate the effects of temperature and alkalization treatments on the release of ammonia and ammonia recovery (AR) from cow manure and to characterize the chemical properties of the resultant effluents. In a closed glass reactor, 100 g of fresh cow manure was mixed with 100 mL of deionized water and the mixture was treated with various volume of KOH to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Urea and ammonia were previously indicated as suitable animal waste disinfectants [20,21], despite the concerns about ammonia emissions. A combined treatment could solve this problem with alkalinization to achieve sanitization, followed by neutralization to pH = 7.0 to reduce emissions [22]. The potential negative impacts on soil properties and availability of nutrients to crops induced by the application of slurries with low or high pH values would also be avoided [23].…”
Section: Introductionmentioning
confidence: 99%
“…Urea and ammonia were previously indicated as suitable animal waste disinfectants [20,21], despite the concerns about ammonia emissions. A combined treatment could solve this problem with alkalinization to achieve sanitization, followed by neutralization to pH = 7.0 to reduce emissions [22]. The potential negative impacts on soil properties and availability of nutrients to crops induced by the application of slurries with low or high pH values would also be avoided [23].…”
Section: Introductionmentioning
confidence: 99%
“…The alkalization of slurry is another method used to reduce emissions, but it is based on the addition of alkaline additives, that cause the precipitation of phosphorus and an increase in pH, which shifts the equilibrium towards the volatile form NH 3 [14,19]. A so-called stripping technology enables the removal of the growing share of NH 3 in the slurry, which is then captured and concentrated by absorption with concentrated sulphuric acid to produce ammonium-based mineral fertilizers [20,21]. It has been shown that an ammonia recovery rate of more than 90% is possible in cattle slurry at a pH of 12 [20].…”
Section: Introductionmentioning
confidence: 99%
“…A so-called stripping technology enables the removal of the growing share of NH 3 in the slurry, which is then captured and concentrated by absorption with concentrated sulphuric acid to produce ammonium-based mineral fertilizers [20,21]. It has been shown that an ammonia recovery rate of more than 90% is possible in cattle slurry at a pH of 12 [20]. The adjustment of a targeted pH value can be very challenging, as the pH value of stored slurry may fluctuate widely over time due to an increase or decrease in the buffer capacity of the four main buffer systems within slurry, which are volatile fatty acid (VFA) buffer (predominantly CH 3 COOH/CH 3 COO − ), carbonic acid-bicarbonate buffers (H 2 CO 3 / HCO 3 − and HCO 3 − /CO 3 2− , hereafter only HCO 3 and CO 3 2buffer) and ammonia buffer (NH 4 + /NH 3 ) (shown in Figure 1) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its competitive price, H 2 SO 4 is the most commonly used acid during NH 3 washing step. Nevertheless, other agents such as nitric acid, boric acid, organic acids and gypsum have also been tested to recover NH 3 from the gas phase, generating scrubbing salts ( Abouelenien et al, 2009 ; Jamaludin et al, 2018 ; Mohammed-Nour et al, 2019 ; Sigurnjak et al, 2019 ). To our knowledge, Benas is the first AD plant that installed an industrial vacuum NH 3 stripping and scrubbing unit relying on gypsum.…”
Section: Resultsmentioning
confidence: 99%